Accuracy of volume and pressure delivery by mechanical ventilators in use in neonatal intensive care units: A quality control study. Issue 8 (27th May 2020) - Ottaviani, Valeria; Veneroni, Chiara; Dell'Orto, Valentina; Lavizzari, Anna; Ventura, Maria Luisa; Tossici, Marta; Maroszynska, Iwona; Mosca, Fabio; Tagliabue, Paolo; De Luca, Daniele; Dellacà, Raffaele L.
Abstract: Objective: Despite technical specifications of neonatal mechanical ventilators (MVs) guarantee clinically irrelevant discrepancies between the set and the delivered values of ventilation parameters, previous studies reported large deviations. Most studies characterized performances of a given model/brand by studying a single device, disregarding possible intramodel differences, and leaving the accuracy of the ventilation parameters effectively delivered in clinical settings unknown. The aim of this study was to evaluate the real‐life accuracy of pressure and volume parameters delivered by neonatal ventilators ready to be used on patients in neonatal intensive care units (NICUs). Study Design: In vitro study. Subjects Selection: Neonatal ventilators (n = 33 of 8 different models) available in four European NICUs. Methodology: The MVs were connected to a test lung (resistance = 50 cmH2 O*s/L, compliance = 0.35 mL/cmH2 O) provided with pressure and flow sensors. MVs were tested over two different ventilation modes randomly: (a) pressure controlled (PC) with a peak inspiratory pressure (PIP) of 22 cmH2 O, and (b) PC with volume targeted ventilation (VTV) with a tidal volume ( VT ) of 6 mL. In all tests, positive end‐expiratory pressure (PEEP) was set to 6 cmH2 O, respiratory rate to 45 breaths/min, inspiratory time to 0.33 seconds, and oxygen fraction to 0.3. Results: During PC the median (min‐max) values delivered were: PEEP = 5.84(4.95‐6.48) cmH2 O, PIP = 21.63(20.04‐22.62) cmH2 O. During VTV, VT was 5.94(4.63‐8.01) mL. VT was considerably variable, ranging from −22% to +33% of the set and displayed values. Differences in accuracy among devices of the same model were comparable to those found among different models. Conclusions: Our findings suggest that loss of accuracy in ventilation variables is likely related to daily use of the devices rather than weakness in the design or manufacturing process, urging the improvement of maintenance and quality control procedures to preserve the performances of neonatal MVs during their entire lifespan.